THE INFLUENCE OF COLOR AND LIGHT ON INTERIOR SPACES: AN ANALYSIS OF PSYCHOLOGICAL AND DESIGN PERSPECTIVES - Marguba Madumarova (Galaxy International Interdisciplinary Research Journal, 2023)
This scientific paper aims to examine the importance of color and light in interior design and its impact on people’s perception and wellbeing. Examining the psychological and design aspects, this study seeks an integrated understanding of how color and light can be used effectively to create visually attractive and functional interiors. A large-scale study of relevant literature reveals that color and light play a crucial role in shaping the overall environment, mood and functionality of the interior. Consequently, this article emphasizes the importance of choosing suitable color schemes and light solutions to optimize the desired results of internal design projects.